A nonparametric analysis of regional unemployment dynamics in Britain - Marco Bianchi; Gylfi Zoega (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
This paper estimates the probability distribution of relative county unemployment in Britain for the years 1981-1995. We find that the distribution is unimodal in all years, with a falling variance between 1989 and 1994. We use bootstrap methods to determine critical values for the two tails of the distribution, and analyse intra-distribution dynamics. An unemployment transition is defined as a move between a tail and the centre of the distribution (and vice versa). We calculate transition probabilities and find that the probability of leaving any given state is very low. We also find that high (low) unemployment regions have a higher probability of entering a state of lower (higher) unemployment than a state of higher (lower) unemployment.
urn:nbn:de:kobv:11-10064736
Keywords: E24; R12; C14; 330; panel data; nonparametric analysis; Regional unemployment; asymmetric effects in the persistence of transition dynamics